Multimedia Evaluation of EMT-Paramedic Assessment and Management of Pediatric Respiratory Distress. (31st August 2021) - Schroter, Stephanie; Thomas, Danny; Nimmer, Mark; Visotcky, Alexis; Fraser, Raphael; Colella, M. Riccardo; Browne, Lorin R.
Abstract: Background: The prehospital care of asthma, bronchiolitis and croup is directed by evidence-based Emergency Medical Services (EMS) protocols. Determining the appropriate intervention for these conditions requires Emergency Medical Technicians-Paramedics (EMT-Ps) to correctly differentiate asthma/bronchospasm, bronchiolitis, and croup. The diagnostic accuracy of EMT-Ps for these pediatric respiratory distress conditions is unknown. Objective: We hypothesized increasing provider age, years of provider experience, higher volume of pediatric cases, self-reported comfort with pediatric patients, and having children of one's own would be associated with increased accuracy in diagnosis on a validated multimedia questionnaire. Methods: This is a cross-sectional study of paramedics from a single EMS agency who completed a validated, case-based questionnaire between July and September 2018. The multimedia questionnaire consisted of four cases, each of which included patient videos and lung sound recordings. Paramedics were asked to assess the severity of distress and ascribe the correct diagnosis and prehospital intervention for each case. Each paramedic completed the questionnaire independently. We defined high questionnaire performance a priori as correctly identifying the diagnosis for ≥75% of cases and used multivariate regression to assess factors associated with high questionnaire performance. Provider age and EMS experience were reported in years and analyzed as continuous variables. Volume of pediatric cases was dichotomized to <1 and ≥1 case per shift and having children was dichotomized to either having children or not having children. Results: Of 514 paramedics, 420 (82%) completed the questionnaire. Overall, paramedics correctly assessed the severity of respiratory distress 92% of the time. However, they only ascribed the correct diagnosis 50% and selected the correct intervention(s) 38% of the time. Increasing age, years of experience, higher volume of pediatric cases, self-reported comfort with pediatric patients, and having children of their own were not associated with questionnaire performance. Conclusion: Paramedics accurately assessed severity of distress in multimedia cases of asthma/bronchospasm, bronchiolitis and croup in children, but showed significant room for improvement in correctly identifying the diagnosis and in selecting appropriate intervention(s). Age, years of EMS experience, higher volume of clinical pediatric cases, self-reported comfort with pediatric patients, and having children of their own were not associated with questionnaire performance.